Spontaneous Evisceration, or “Burst Abdomen,” in Patient with Prior Flood Syndrome Surgical Repair - Matthias Barden; Dustin Marinelli; Kirsten Cable (Clinical Practice and Cases in Emergency Medicine)
Case Presentation: We present an image and discussion of spontaneous evisceration, or “burst abdomen,” from an anterior abdominal wall hernia. A 61-year-old female with prior history of alcoholic cirrhosis and ascites presented to our emergency department with frank evisceration of multiple loops of small bowel from an open anterior abdominal wall dehiscence. Approximately one year prior to this visit she had also been seen in our department for spontaneous rupture of the skin overlying an umbilical hernia and large-volume external leakage of ascites (Flood syndrome 1). She required surgery to repair the abdominal wall at that time but had subsequently developed a new ventral hernia extending from the umbilicus across a large portion of her left lower abdomen as well as several other postoperative complications. On the day of presentation, she suffered dehiscence of that one-year-old surgical site resulting in spontaneous evisceration of her small bowel. She was transferred to a facility with acute care surgical capabilities where she remained in critical condition. Discussion: Spontaneous evisceration from abdominal wall dehiscence is a devastating surgical complication. It tends to occur in the immediate postoperative period but has been reported to occur years later. This patient likely suffered from delayed burst abdomen due to multiple comorbidities and postoperative complications.